Penggunaan Aplikasi Google Meet dalam Menunjang Keefektifan Belajar Daring Masa Pandemi Covid-19 di SMA Negeri 3 Pekanbaru - Piki Setri Pernantah; Nova Nova; Annisa Suci Ramadhani (Pedagogi: Jurnal Ilmu Pendidikan, 2021)
So that online learning can run well, teachers are expected to be able to take advantage of technology in their learning. One of the uses of technology is using learning application media. At SMA Negeri 3 Pekanbaru, they have used the Google Meet application, Google Classroom, and Whatsapp in the online learning process. From several observations in the field, SMA Negeri 3 Pekanbaru teachers are more likely to use the Google Meet application in online learning. The Google Meet application is considered to be easier and more effective in delivering learning material. This study aims to describe the perceptions of students and teachers and the process of using the Google Meet application in online learning at these schools. This type of research is a qualitative research with a descriptive-analysis approach. Based on field research, it is known that the Google Meet application is classified as more effective than other learning application media. The use of Google Meet which is of interest to students and teachers certainly supports the implementation of effective online learning during the COVID-19 pandemic.